INBORN ERRORS OF METABOLISM SCREENING AND SCOPE OF GC-MS; A REVIEW - Sharma, Preeti; KUMAR, PRADEEP; SHARMA, RACHNA; PS, DHOT (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Inborn errors of metabolism (IEM) are a group of disorders arising from inherited errors of biological pathways, which can be of Intoxication type (accumulation of intermediates of metabolism) or energy deficiency type pathways1. Certain pathological alterations in normal catabolic path of aminoacids, carbohydrates, lipids or biogenic amine often result in abnormal excretion pattern of organic metabolites that are normally absent or present in very small concentration2. These IEM currently in human beings exceed 500. Out of them 100 alone are the errors of aminoacids metabolism. Among these Phenylketonuria and Maple Syrup Urine Diseases are severely inherited3. GC-MS in itself is invaluable tool in the field of IEM. Gas Chromatography coupled with mass spectrometry (GC-MS) is typically used to quantify and identify primarily nonpolar metabolites influencing the practice which are less than 1 KD in mass. GC/MS combines the separating power of Gas Chromatography (GC), with the detection power of mass spectrometry.